REASON, EXPERIENCE, AND LANGUAGE TO ACQUIRE KNOWLEDGE (IN WESTERN AND ISLAMIC PERSPECTIVES) - Rahardjo, Mudjia (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
The system of knowledge acquisition is one of the most important topics in philosophical debates since ancient Greek. According to the Western philosophical worldview, as the universally accepted method, there are two schools of thought to acquire proper knowledge; rationalism and empiricism. Rationalism assumes that sound reason is the main human potential to acquire knowledge that constitutes a priori knowledge, while empiricism relies on sensory abilities constituting a posteriori or empirical knowledge. In addition, Islam offers intuition or instinct as another source of knowledge that creates intuitive knowledge, be it empirical or spiritual. The knowledge gained is then developed through language symbols, from being personal to finally public knowledge. Through language, knowledge is inherited from one generation to the next. However, due to its limitations, language is not able to symbolize all types of knowledge. Consequently, there are two kinds of knowledge; articulated (explicit) knowledge and unarticulated (tacit) knowledge. Nevertheless, despite their sharp differences, both the Western and Islamic worldviews assume that knowledge acquisition is the field of a speculative philosophical endeavor which is hard to get a satisfying answer, though it is not impossible.